HOW MUCH HAS THE COVID-19 PANDEMIC CHANGED US? THE EXPERIENCE OF THE CLINIC FOR MENTAL DISORDERS "DR LAZA LAZAREVIĆ" - Stašević - Karličić, Ivana (Srpski medicinski časopis Lekarske komore, 2021)
In order to preserve and improve public health and following the recommendations of the World Health Organization (WHO), the Clinic for Mental Disorders "Dr Laza Lazarevic" in cooperation with the Ministry of Health of the Republic of Serbia developed a strategy for mental health during the COVID-19 pandemic. This paper briefly presents some specific activities that the Clinic for Mental Disorders "Dr Laza Lazarevic" carried out during the current pandemic COVID-19.